Synthesis, characterization and crystal structure of racemic vanadyl and uranyl salen-type complexes - Mello, Lucas dos S.; da Cruz Jr, José W.; Bucalon, Daniel H.; Romera, Sandra; dos Santos, Mirian P. [UNESP]; Lião, Luciano M.; Vizotto, Luciana; Martins, Felipe T.; Dockal, Edward Ralph (Elsevier, 2021)
Synthesis, characterization and crystal structure for racemic ONNO Schiff base ligand 3-OMe-t-salcn (trans-N,N’-bis(3-methoxysalicylidene)-1,2-cyclohexanediamine) and its vanadyl and uranyl complexes are reported. Both complexes were mononuclear, with the Schiff base ligand occupying equatorial coordination sites and the oxo ligands occupying apical positions. Crystal structures were solved in P21/n and P21/c space groups for uranyl and vanadyl complexes, respectively, presenting both (R,R) and (S,S) enantiomers in 1:1 ratio in the same packing unit, which also contain three water molecules. Vibrational, electronic and nuclear magnetic resonance spectroscopies were recorded and are discussed. Gaussian analysis was conducted in order to help electronic spectral attribution.
Keywords: Racemic mixture; Schiff base; Single-crystal X-ray structure; Uranium(VI) complex; Vanadium(IV) complex